Islamic Ethics In Sustainable Environmental Resource Management - Bachrul Ulum; Nur Hasanah Mahnan; Fathul Ihsani (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
God has given people two gifts or gifts, to be specific the assets that exist inside themselves and the normal assets that encompass them. People are given the order by Allah to possess the earth since he has the force of caliph to have the option to deal with its items. God believes people should oversee normal abundance, dislike the past tenants (the jinn) who generally cause harm. God needs the abundance on earth that He has offered to people to be appropriately and gainfully developed. The efficiency of nature is exceptionally reliant upon the imaginative utilization of the power that exists in people. In this manner, people should work tirelessly, investigate the regular abundance that God has gave to them. For a Muslim, it is unlawful not to work despite the fact that he can work. There are numerous regular assets that can be overseen by people. Beginning from land, water, plants, creatures, mines, twist, even the sun and moon. Everything is nature that fans out its wealth for people. Notwithstanding, people should recall that the genuine proprietor of this abundance is Allah SWT. In this manner, in dealing with these normal assets, people should consent to the rules that have been framed by Allah in His Shari'a. Shari'a needs nature not to be harmed or its advantages to be squandered. Any activity that can disturb the equilibrium of nature is completely denied by the Shari'a.